COMPARISON OF DRONE MARKET DEVELOPMENT IN OFFSHORE WIND FARM SECTOR BETWEEN JAPAN AND CHINA - Aisya Bella Satu Pertiwi; Jan Noeverman; Anis Chariri (Diponegoro Journal of Accounting, 2022)
With the passage of time, the existence of drones became a common concept around the world and drones started to be introduced into civilian use. With their ability to collect data and transport loads, drones are re-shaping the way society thinks. Companies, organizations or individuals slowly respond to these new opportunities – using drones to help save time, increase revenue, and lower risks to workers in industries.Overall, this study will concentrate on the topics of drone market development and offshore wind farms, including the use of drones in the offshore wind farm sector. Japan and China would be the area of this study because they have better prospects in the concept of energy compared to other countries in Asia and have intention to change into renewable energy. Thus, a comparison was made to see the results, and it can be concluded that  in terms of the one that is more likely to develop, China has a better chance of being the leading drone market in the offshore wind farm sector.